The Theocons: Secular America Under Siege - Linker D.; Linker Damon (New York London Toronto Sydney Auckland Doubleday, 2006)
An essential history of the influential men who have spearheaded the movement to erode the wall separating church and state.Beginning as far-left radicals during the 1960s, the theocons in Damon Linker s book (including Richard John Neuhaus, Michael Novak, and George Weigel) gradually transitioned to conservatism when they grew frustrated with the failures of the decade s revolutionary goals. Linker shows how, starting during the Reagan administration, they worked to forge a Christian alliance between Evangelical Protestants and Conservative Catholics. By injecting the language of faith into political life, this movement appealed to a wide swath of voters and ultimately played a central role in the election of George W. Bush. The Theocons is an absorbing and revelatory look at an ideological crusade that every American needs to know about.
Keywords: 32